Spatial and temporal changes of Hg in Jiaozhou Bay 1990. Issue 4 (February 2019) - Yang, Dongfang; Lin, Dong; Wang, Qi; Zhang, Longlei; Li, Haixia
Abstract: Using investigation on Mercury (Hg) in May and August 1990, this paper analyzed the spatial and temporal variations of Hg contents in Jiaozhou Bay. Results showed that Cd contents in both surface and bottom waters were in order of spring > summer. In waters in the bay mouth, the variation ranges of Hg contents in surface waters (0.053-0.208 μg L -1 ) were closed to what in bottom waters (0.053-0.204 μg L -1 ) due to the rapid and continuous sediment of Hg to bottom waters. The source strength and occurring position of different Hg source were different. However, in any position and in any season, the horizontal distributions of Hg contents in surface waters and bottom waters were consistent. That's the outcome of vertical water's effect.